Considerations in the provision of teleconsultations for outpatient obstetric anaesthesia care during the Covid-19 pandemic - Leonard Wei Wen Loh (SAGE Publishing, 2021)
Evidence has emerged that pregnant women who contract coronavirus disease 2019 (Covid-19) are at increased risk of certain forms of severe illness as well as complications requiring intensive care unit admission and resultant mortality. Teleconsultations can facilitate continuing care for obstetric patients during the Covid-19 pandemic while reducing their risk of exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In this short report, we share our experience in the provision of teleconsultations for ambulatory obstetric anaesthesia patients in our high-risk obstetric anaesthesia clinic during the Covid-19 pandemic. Appropriate labour analgesia or anaesthesia plans were able to be formulated and communicated to the patients by teleconsultation, resulting in no delay or compromise in their peripartum care. Both patients and clinicians reported satisfaction with the teleconsultation process and outcome. The considerations and challenges in setting up a teleconsultation service as well as the factors in favour of teleconsultation are also explored.